2014
DOI: 10.4067/s0718-58392014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of cell wall and cuticle related genes during fruit development of two sweet cherry cultivars with contrasting levels of cracking tolerance

Abstract: Rain-induced cracking before harvest is the major cause of crop loss in sweet cherry (Prunus avium [L.] L.) In order to better understand the relationship between cherry fruit cracking and gene expression, the transcriptional patterns of six genes related to cell wall modification and cuticular wax biosynthesis were analyzed during fruit setting (FS), fruit color change (FC) and fruit ripening (FR), employing two contrasting cultivars: the cracking resistant 'Kordia' and the cracking susceptible 'Bing'. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 36 publications
8
39
1
1
Order By: Relevance
“…The accumulation of galacturonate in skin tissues could be associated with the activation of βgalactosidase and the solubilization of pectin [34]. This observation is consistent with results previously obtained [35], who found that the up-regulation of various cell-wall genes, such as βgalactosidase in sweet cherry fruit contribute to a greater flexibility and elasticity of the skin, which in turn is reflected by a lower percent of cracking. In this regard, cracking-susceptible sweet cherry cultivars release higher level of soluble pectin fractions during hydrocooling conditions [25].…”
Section: Discussionsupporting
confidence: 91%
“…The accumulation of galacturonate in skin tissues could be associated with the activation of βgalactosidase and the solubilization of pectin [34]. This observation is consistent with results previously obtained [35], who found that the up-regulation of various cell-wall genes, such as βgalactosidase in sweet cherry fruit contribute to a greater flexibility and elasticity of the skin, which in turn is reflected by a lower percent of cracking. In this regard, cracking-susceptible sweet cherry cultivars release higher level of soluble pectin fractions during hydrocooling conditions [25].…”
Section: Discussionsupporting
confidence: 91%
“…The accumulation of galacturonate in skin tissues could be associated with the activation of βgalactosidase and the solubilization of pectin [31]. This observation is consistent with results previously obtained [32], who found that the up-regulation of various cell-wall genes, such as βgalactosidase in sweet cherry fruit contribute to a greater flexibility and elasticity of the skin, which in turn is reflected by a lower percent of cracking. In this regard, cracking-susceptible sweet cherry cultivars release higher level of soluble pectin fractions during hydrocooling conditions [22].…”
Section: Physiological Traits and Skin Metabolites In Relations To Crsupporting
confidence: 91%
“…To evaluate cracking tolerance, fruit of similar size from different treatments were sorted visually to remove any damaged fruit. A set of 25 stem-attached fruits from each biological sample (tree) was placed in distilled water at 20 °C for 6 h. Cracking index (CI) was calculated by the method used by Balbontín et al (2014), based in the formula reported by Christensen (1972). CI = ((6a + 5b + 4c + 3d + 2e+1f) (MPV)-1) 100 where a, b, c, d, e and f represent the number of cracked fruit at 1, 2, 3, 4, 5 and 6 h respectively, MPV is maximum possible value (25 fruits × 6 h).…”
Section: Cracking Tolerance and Fruit Quality Assessmentsmentioning
confidence: 99%